Perancangan Ulang Antarmuka Pengguna Sistem e-Management PKL SMKN 6 Malang dengan Metode Goal Directed Design - Rosita Devi Ramadhani; Hanifah Muslimah Az-Zahra; Prima Zulvarina (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMKN 6 Malang is one of the Vocational Schools in Malang City. To facilitate the process of implementing street vendors, SMKN 6 Malang has a website called "MasterWeb". The "MasterWeb" site in its implementation is still not optimal. This is based on observation, interviews, and initial testing conducted on students of SMKN 6 Malang. This study aims to determine the results of a comparison of the usability of the "MasterWeb" site with the usability results of the redesign of the "SEPKL" site. This research was conducted by redesigning the street vendor site user interface using the Goal Directed Design (GDD) method. Design with the GDD method will directly involve users and stakeholders so that the design results are more appropriate. In the initial testing phase, testing was carried out using the interview method and the System Usability Scale (SUS) questionnaire to determine whether the "MasterWeb" site really requires a redesign, what problems exist, and determine what is the best solution to solve these problems from the user's point of view. In the initial test using SUS, the final value was 57.75. After the interface design is complete, a final test is carried out using Usability Testing and the System Usability Scale. In testing the Usability Testing Effectiveness aspect, the final score was 87.5 and the Efficiency Aspect was 0.197 goal/sec. While on the satisfaction aspect, the Questionnaire System Usability Scale was used and the final score obtained was 82.75.